Aligning Institutions and Industrial Strategy: A Transformation Framework for Georgia’s European Future - Moghimi, Bahman (European Scientific Journal, ESJ, 2026)
Georgia’s industrial challenge is not the absence of strategies, but the absence of a credible transformation architecture that can convert institutional reform into firm upgrading, export capacity, and durable competitiveness. This paper develops GIPTM-7, a seven-pillar industrial transition framework tailored to a small open economy pursuing Euro-Atlantic integration. Methodologically, it combines a systematic literature review, thematic synthesis, Georgia-specific institutional contextual analysis, and scenario-based stress testing to derive and interrogate the model’s internal logic. The framework identifies seven mutually reinforcing industrial strength domains: transparent flow and transparent governance and institutions and rule of law; entrepreneurial and private-sector capacity; strategic state policy and industrial finance; knowledge and human capital systems; infrastructure and connectivity; sustainability and industrial resilience; and global integration and EU alignment. Scenario analysis (EU accession acceleration, diversified trade reorientation, stagnation, and institutional-weakness stress tests) demonstrates that progress is non-linear: institutional credibility and execution capacity condition the productivity of patient capital, while private-sector upgrading determines whether integration produces complexity rather than mere trade volume. The paper concludes with sequenced policy implications and an implementation roadmap that prioritize credibility, operational capacity formation, and EU-aligned industrial governance. GIPTM-7 offers a practical, country-grounded template for organizing industrial policy around interdependent capabilities rather than isolated reforms.